CEO Turnover, Earnings Management, And Family Ownership (Empirical Study On Property And Real Estate Companies Listed On The Indonesia Stock Exchange, 2020-2022) - Titi Aslah; Jhon Tarigan; Andhika Napitupulu (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
This study aims to analyze and provide empirical evidence of the effect of CEO turnover on earnings management, with family ownership as a moderating variable, in property and real estate companies in Indonesia. The hypotheses tested are: (1) CEO turnover is positively related to earnings management, and (2) family ownership strengthens the relationship between CEO turnover and earnings management. This study uses data from property and real estate companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022, selected on the criteria that they published audited financial statements denominated in rupiah, accessible on the IDX website. Samples were obtained through purposive sampling, and the data were analyzed using multiple regression analysis. The results show that (1) CEO turnover is related to earnings management, so the first hypothesis is accepted, and (2) family ownership significantly strengthens the relationship between CEO turnover and earnings management, so the second hypothesis is accepted.